2022
DOI: 10.3390/nu14112273
|View full text |Cite
|
Sign up to set email alerts
|

Observational and Genetic Associations of Modifiable Risk Factors with Aortic Valve Stenosis: A Prospective Cohort Study of 0.5 Million Participants

Abstract: Background: Observational studies have shown that modifiable risk factors are associated with aortic valve stenosis (AVS). However, the causality behind these associations remains largely unknown. Objectives: To explore the associations of modifiable risk factors, including metabolic factors, biochemical measures, education, and lifestyles with AVS and their potential causal associations. Methods: We enrolled 361,930 British white people with genetic data in the UK biobank. Cox proportional risk regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…In a prospective cohort study of 361 930 people with genetic data in the UK Biobank, a total of 1602 participants developed aortic valve stenosis during an 8.4-year follow-up. 24 Cox proportional risk regression models were used to estimate the HRs between 28 modifiable risk factors and aortic valve stenosis.…”
Section: Valvular Diseasesmentioning
confidence: 99%
“…In a prospective cohort study of 361 930 people with genetic data in the UK Biobank, a total of 1602 participants developed aortic valve stenosis during an 8.4-year follow-up. 24 Cox proportional risk regression models were used to estimate the HRs between 28 modifiable risk factors and aortic valve stenosis.…”
Section: Valvular Diseasesmentioning
confidence: 99%
“…Conversely, another study found phosphate, but not calcium or vitamin D, to be significantly related to aortic valve stenosis incidence [116]. A large prospective observational Chinese study suggested a potential protective role of vitamin D in relation to degenerative aortic valve stenosis [117].…”
Section: Aortic Stenosismentioning
confidence: 96%
“…Previous studies have shown that age, obesity, smoking, coffee intake, hypertension, diabetes, kidney disease and bicuspid aortic valve are associated with an increased risk of aortic valve stenosis [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. The Cardiovascular Health Study is a large-scale prospective, longitudinal, population-based study of the elderly, aimed at determining risk factors of aortic sclerosis and stenosis [ 69 ].…”
Section: Risk Factors Of Aortic Valve Calcificationmentioning
confidence: 99%